Tailoring type-II all-in-one buried interface for 1.635V-voltage, all-inorganic CsPbBr3 perovskite solar cells. (1st June 2022) - Yao, Xinpeng; He, Benlin; Zhu, Jingwei; Ti, Junjie; Cui, Lifang; Tui, Rui; Wei, Meng; Chen, Haiyan; Duan, Jialong; Duan, Yanyan; Tang, Qunwei
Abstract: Precise manipulation on buried interface of perovskite film highly determines the photovoltaic performance of perovskite solar cells (PSCs). Herein, we demonstrate a SnO2 -SnS2 heterojunction nanocrystal as an efficient electron transfer material to heal the defective interface for planar all-inorganic CsPbBr3 PSCs. Arising from the matched lattice distance of SnS2 with SnO2 and CsPbBr3, an all-in-one SnO2 -SnS2 -CsPbBr3 interface is fabricated, in which SnS2 plays a role of "bridge" to connect incompatible interface. Consequently, the charge recombination loss is minimized owing to the Type-II band alignment and epitaxial growth induced defect reduction, achieving a remarkable efficiency of 10.72% with a high open-circuit voltage of 1.635V. Considering the high tolerance to high humidity (80%) for 700 h and high temperature (80 °C) over 30 days, these preliminary results can provide a new perspective for the rational design of ideal charge transfer materials to improve the efficiency and stability of PSCs. Graphical Abstract: Arising from the matched lattice distance of SnS2 with SnO2 and CsPbBr3, an all-in-one SnO2 -SnS2 -CsPbBr3 interface is formed, playing a role of "bridge" to connect incompatible buried interface. The results demonstrate that the regulated interfacial energetics and reduced defects significantly improve the device performance and stability. ga1 Highlights: An all-in-one SnO2-SnS2-CsPbBr3 interface as buried "bridge" is fabricated. Type-II band alignment and epitaxial growth induced defect reduction is realized. All-inorganic CsPbBr3 PSC achieves a champion efficiency of 10.72% with VOC of 1.635V. The unencapsulated device shows excellent tolerance under high humidity and temperature.